2005
DOI: 10.1074/jbc.m506289200
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin but Not Adsorbed Fibrinogen Supports Fibronectin Assembly by Spread Platelets

Abstract: We investigated the assembly of soluble fibronectin by lysophosphatidic acid-activated platelets adherent to fibrinogen or fibrin. More fibronectin was assembled by activated platelets spread on fibrin matrices than by platelets spread on adsorbed fibrinogen. The difference between platelets adherent to fibrinogen and fibrin occurred under both static and flow conditions. Similar differences were seen in binding of the 70-kDa N-terminal fragment of fibronectin that recognizes fibronectin assembly sites on adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 64 publications
4
9
0
Order By: Relevance
“…Fibronectin, a protein that forms part of the extracellular matrix, is also abundant in plasma and mediates platelet aggregation by binding β 3 integrins and tethering adjacent platelets (82, 83). It has been reported that incorporation of plasma fibronectin into fibrin clots enhances metastasis to the lungs (84).…”
Section: Pclp1 a Selectin Ligand Involved In Platelet–tumor Interactionmentioning
confidence: 99%
“…Fibronectin, a protein that forms part of the extracellular matrix, is also abundant in plasma and mediates platelet aggregation by binding β 3 integrins and tethering adjacent platelets (82, 83). It has been reported that incorporation of plasma fibronectin into fibrin clots enhances metastasis to the lungs (84).…”
Section: Pclp1 a Selectin Ligand Involved In Platelet–tumor Interactionmentioning
confidence: 99%
“…Furthermore, plasma FN can also be bound and then assembled into a high-molecular-weight multimeric matrix on the platelet surface. Platelet activation by thrombin induces increased cell-surface expression of the major platelet integrin αIIbβ3, which binds and assembles FN via a fibrin-independent mechanism [38-44]. Platelets also express a lower number of α5β1 and αvβ3 receptors on their surface, which mediate platelet adhesion [45].…”
Section: Introductionmentioning
confidence: 99%
“…Aggregated platelets can also assemble FN via a fibrin-dependent pathway [44]. The polymerization of fibrin into a three-dimensional network has been shown to be essential for FN assembly, as the γ chain of unprocessed fibrinogen signals via αIIbβ3 to inhibit this process [38]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We finally asked whether our findings regarding Fn assembly could be generalized to specific thrombus sites. Besides Fn, we selected fibrin as the major clot component since spreading on fibrin but not fibrinogen supports Fn matrix assembly by platelets (Jaehyung Cho et al 2005). Platelets on fibrin coatings showed the typical αIIbβ3-dependent contractile phenotype (Lickert et al 2018) and formed Fn fibrils mainly localized in the periphery of the cell ( Figure 6a).…”
Section: The Dimensionality Of the Fibronectin Fibril Network Is Difmentioning
confidence: 99%